EU-US Transatlantic Partnership in yhe Context of Global Competition - Cristian Romeo Spataru; Cristian Constantin Popescu (Ovidius University Annals: Economic Sciences Series)
Historically, the "partnership" between the EU and the USA has unfolded on multiple levels - economic, technological, social, cultural, and strategic - and is rooted in shared values such as democracy, fundamental rights, and the rule of law. Multilateral forums, especially NATO, strengthen this bond. The core strength of transatlantic relations lies in the deep economic integration between the two major economies, reflected in robust trade and mutual investments that benefit both. This paper focuses on the economic and financial aspects and their impact on the partnership. EU-USA cooperation's shared values and mutual benefits outweigh their occasional disagreements or misunderstandings. Therefore, signing a comprehensive collaboration in the future (not merely a sequential or sectoral one) should be a priority for both parties. Will Trump agree?